2012
DOI: 10.1007/s00464-011-2113-3
|View full text |Cite
|
Sign up to set email alerts
|

Pylorus- and spleen-preserving total pancreatoduodenectomy with resection of both whole splenic vessels: feasibility and laparoscopic application to intraductal papillary mucin-producing tumors of the pancreas

Abstract: PpSpTPD with segmental resection of both splenic vessels is feasible and safe. Even a minimally invasive approach can be indicated in selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 20 publications
0
30
0
1
Order By: Relevance
“…Studies suggest the minimally invasive approach is not only feasible but equivalently efficacious and safe: with similar perioperative morbidity and mortality (6)(7)(8)(9)(10)(15)(16)(17)(18)(19). In particular, the minimally invasive approach to distal pancreatectomy has been widely accepted and clearly demonstrated advantages such as reduced blood loss, reduced overall complication rate, reduced surgical site infection and shorter hospital length of stay (7)(8)(9)(10)17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies suggest the minimally invasive approach is not only feasible but equivalently efficacious and safe: with similar perioperative morbidity and mortality (6)(7)(8)(9)(10)(15)(16)(17)(18)(19). In particular, the minimally invasive approach to distal pancreatectomy has been widely accepted and clearly demonstrated advantages such as reduced blood loss, reduced overall complication rate, reduced surgical site infection and shorter hospital length of stay (7)(8)(9)(10)17).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the minimally invasive approach to distal pancreatectomy has been widely accepted and clearly demonstrated advantages such as reduced blood loss, reduced overall complication rate, reduced surgical site infection and shorter hospital length of stay (7)(8)(9)(10)17). Laparoscopic TP remains a rare procedure, but has shown recent increased use in high volume centers and similarly shown to be safe and feasible (15,16,18,19). A comprehensive review of our initial experience revealed those receiving LTPIAT had significantly shorter hospitalization with median length of stay being 10.5 compared to 14 days for open surgery as well as significant decrease in median postoperative dose of opiate on discharge in the laparoscopic group compared to open (16).…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17] In selected patients, a short operative time (270 and 360 minutes) and minimal blood loss (200 and 300 mL) can be obtained and are comparable and even lower than with an open approach. 10,18 Although many lagers reports on laparoscopic PD had been published, 19,20 this technique is still not used extensively because of the complexity of both dissection but especially the reconstruction phase.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Although laparoscopic distal pancreatic resection and less frequently pancreaticoduodenectomy (PD) are increasingly performed, only a few cases of laparoscopic TP (LTP) have been reported. [14][15][16][17] The laparoscopic approach may have many advantages for this indication compared with an open approach or other types of laparoscopic pancreatic resections.…”
Section: Introductionmentioning
confidence: 99%
“…Only minimal to moderate perigastric fundal varices were noted without gastrointestinal bleeding. Thus, PpSpTPD with segmental resection of both splenic vessels can be indicated in selected patients [30]. The procedure has also been performed laparoscopically [31].…”
Section: Modified Surgical Techniquesmentioning
confidence: 99%